RATU BAGUS KUNING - Abdullah, Ardi; Desfiarni, Desfiarni (SENDRATASIK UNP, 2019)
AbstractÂ The dance work "Ratu Bagus Kuning" aims to realize a dance work that originate from a story in South Sumatra, especially Palembang. The idea of the dance work "Ratu Bagus Kuning" originated from the desire of the choreographer to make a dance claim originating from Palembang folklore. The form of presentation in the dance work "Ratu Bagus Kuning" is a symbolic representational. This dance work tells the story of Princess Mulya Syarifah Mahaniâ€™s journey in spreading Islam in the city of Palembang. In the art work "Ratu Bagus Kuning", there is a moral value to connoisseurs of art that everything we do may not be acceptable to people around us, even though it is a kindness. Obstacles in life must always be present in everything that we do, but the kindness must still be fought forKeywords: Dance Ratu Bagus Kuning, Art Perform